Plasma‐derived FVIII/VWF complex shows higher protection against inhibitors than isolated FVIII after infusion in haemophilic patients: A translational study. Issue 5 (2nd June 2022) - Bravo, Maria Isabel; Pérez, Alba; Raventós, Aida; Grancha, Salvador; Jorquera, Juan Ignacio; Butta, Nora Viviana; Álvarez‐Román, Maria Teresa; Costa, Montserrat; Willis, Todd; Jiménez‐Yuste, Victor
Abstract: Introduction: Presence of von Willebrand factor (VWF) in FVIII concentrates offers protection against neutralizing inhibitors in haemophilia A (HA). Whether this protection is more evident in plasma‐derived (pd) FVIII/VWF or recombinant (r) FVIII concentrates remains controversial. Aim: We investigated the protection exerted by VWF against FVIII inhibitors in an in vivo mouse model of HA exposed to pdFVIII/VWF or to various rFVIII concentrates. Methods: Haemophilia A mice received the different FVIII concentrates after administration of vehicle or an inhibitory IgG purified from a commercial pool of HA plasma with inhibitors and FVIII:C recoveries were measured. Furthermore, using a novel clinically oriented ex vivo approach, Bethesda inhibitory activities (BU) of a commercial pool of HA plasma with inhibitors were assessed using normal plasma, or plasma from severe HA patients, without inhibitors, after treatment with the same concentrates. Results: in vivo studies showed that pdFVIII/VWF offers markedly higher protection against inhibitors when compared with any of the FVIII products without VWF. More importantly, in the ex vivo studies, plasma from patients treated with pdFVIII/VWF showed higher protection against inhibitors ( P values ranging .05‐.001) in comparison with that observed in plasma from patients who received FVIII products without VWF, regardless of the type of product evaluated. Conclusion: Data indicate that FVIII+VWF complexes assembled in the circulation after rFVIII infusion are not equivalent to the naturally formed complex in pdFVIII/VWF. Therefore, rFVIII infused into HA patients with inhibitors would be less protected by VWF than the FVIII in pdFVIII/VWF concentrates.